The Effect Of Work Commitment On Employee Performance At The Sidikalang District Office, Dairi Regency - Muhammad Isa Indrawan; Ira Suryani (Yayasan Multidimensi Kreatif, 2024)
This study aims to examine the effect of work commitment on employee performance at the Sidikalang District Office, Dairi Regency. Work commitment, which includes affective, normative, and ongoing commitments, is considered an important factor in improving employee performance. This study uses a quantitative approach with a causal associative design to test the relationship between the two variables. Data was collected through a questionnaire distributed to 48 employees at the sub-district office, using a saturated sampling technique. Data analysis was carried out using SPSS software version 25.0. The results of the linear regression test show that work commitment has a positive and significant influence on employee performance, with a regression coefficient of 2.187. The coefficient of determination (R²) of 0.654 indicates that 65.4% of the variability of employee performance can be explained by work commitment, while the rest is influenced by other factors that are not studied. The results of the regression analysis showed that work commitment had a positive and significant effect on employee performance at the Sidikalang District Office, Dairi Regency. This can be seen from the t-count value which reached 9.326, greater than the t-table of 2.01290, and the significance value of 0.02 < 0.05., which means that there is a significant influence between work commitment and employee performance. This research contributes to the development of human resource management policies in the government environment to improve employee performance through increasing work commitment.